Everyday Europe : social transnationalism in an unsettled continent /: social transnationalism in an unsettled continent. (2019) - Recchi, Ettore; Favell, Adrian; Apaydin, Fulya; Barbulescu, Roxana, 1983-; Braun, Michael, 1956-; Ciornei, Irina; Cunningham, Niall; Díez Medrano, Juan; Duru, Deniz N; Hanquinet, Laurie; Pötzschke, Steffen; Reimer, David; et al.
No abstract available